ONCE MORE ON TEXT ORGANIZATION MODELS - Ozan Deniz YALÇINKAYA (Fırat University, 2019)
This study, concerned with the “basics” of information development, attempts to examine the applicability of the “new-before/without-given” (further “n-b/w-g”) pattern as an additional resource to F. Daneš’s “given-before-new” (“g-b-n” in furtherance) thematic progression type. Our controversy rests on the claim that “given-before-new” information development model as a linear relation (between “theme” and “rheme”) is not a sufficient condition for organization of texts in different functional styles of language-in-use. Moreover, information “packaging” more than often relies on the purposive aspect of communication and thereby we will query the contention that for a text to be appropriately goal-oriented, not all uses of “given-before-new” model produce effective texts, which, in turn, serves as a basis for our next assumption: “New-before/without-given” model is an independent requirement, not a by-product or an alternative of the “given-before-new” pattern of information development, since it better reflects the relations between text parts in functional terms, and identifying the transition point of a relation, “designs” a more relevant extent of the items related. In this article, the central conceptual properties of the “g-b-n” type of information processing is examined and it is illustrated that the rationale and potential of the “n-b/w-g” model by implementing it in various functional styles and by empirically testing its capacity as well as adequacy to varying communication needs. Comparison-based findings of the two models are addressed as well as the perspective of the problem is drawn attention to. Given the various models, this model aims a more successful communication involving syntactic, semantic and pragmatic elements.